Engagement From the Periphery: Reconceptualizing Adult English Language Learners' Resistance in Developmental Literacy. (November 2020) - Suh, Emily K.
English language learners' nonparticipation and reticence in adult literacy classes are often presented problematically from a deficit lens of student resistance and disengagement . This article draws from an ethnographic case study of Generation 1 learners, who are defined as adult-arrival immigrant learners, transitioning from an adult English as a Second Language class to a developmental literacy class. By examining learners' resistance through a framework of agency enactment, the study bridges the fields of adult literacy and Teaching English to Speakers of Other Languages, both of which support adult-arrival immigrants entering the U.S. education system. The resulting analysis illustrates how Generation 1 learners' acts of resistance can be complex presentations of their literacy identities and their engagement in classroom literacy practices.